2014
DOI: 10.1111/jce.12544
|View full text |Cite
|
Sign up to set email alerts
|

Premature Ventricular Contraction Variability in Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy

Abstract: Statistically significant variation between 24-hour PVC counts is present in the ARVD/C population. However, 24-hour ECG monitoring was sufficient to identify 89.6% of 24-hour periods to the correct grouping based on 2010 Task Force Criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Extension of monitoring duration to capture arrhythmias may be considered. Significant day-to-day variability in PVC burden is noted in patients with ARVD/C, but Camm et al (2015) reported that 24-hr AECG was sufficient to document the required Task Force criterion of over 500 PVCs in nearly 90% of cases, and extension of monitoring to 96 hr increased the number of correct classification to 95.5%.…”
Section: Arrhythmogenic Right Ventricular Dysplasia/ Cardiomyopathymentioning
confidence: 99%
“…Extension of monitoring duration to capture arrhythmias may be considered. Significant day-to-day variability in PVC burden is noted in patients with ARVD/C, but Camm et al (2015) reported that 24-hr AECG was sufficient to document the required Task Force criterion of over 500 PVCs in nearly 90% of cases, and extension of monitoring to 96 hr increased the number of correct classification to 95.5%.…”
Section: Arrhythmogenic Right Ventricular Dysplasia/ Cardiomyopathymentioning
confidence: 99%
“…For assessment of the athlete, the presence of LGE with borderline LV wall thickness would strongly suggest pathologic hypertrophy rather than physiologic adaptation. 28,29 CCT is not often used for the assessment of patients with HCM with a few exceptions. In patients with questionable wall thickness measurements by echocardiography and who are unable to tolerate a CMR, CCT could be considered.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…Both physiologic athletic changes of the RV and pathologic features of patients with ARVC result in increased RV dilatation/volumes compared with LV volumes. 29,34 Echocardiographic measurements of the RV using standard published criteria place many athletes in the abnormal category. 35,36 CMR provides noninvasive evaluation of the RV with more accurate volumetric and functional measurements to differentiate pathologic from physiologic changes of the athlete.…”
Section: Arrhythmogenic Right Ventricular Cardiomyopathymentioning
confidence: 99%
“…However, daily variability in the number of VEs is common and may result in underdiagnosis 47. An association between the total number of VEs per 24 hours and the arrhythmic potential for unstable ventricular arrhythmias has been demonstrated 48.…”
Section: Introductionmentioning
confidence: 99%